Inulin supplementation in feed as a prebiotic for red tilapia Oreochromis sp. - Agustina, Agustina; Susanto, Adi (Jurnal Akuakultur Indonesia, 2024)
The objective of this study was to assess the impact of inulin as a prebiotic in feed on red tilapia (Oreochromis sp.) growth performance, hematological parameters, feed utilization, digestive enzyme activity, and the quantity of lactic acid bacteria in the intestine. This study has a fully randomized design with four treatments and three replications, namely inulin at doses of 0, 1, 2, and 4 g/kg feed. One-way ANOVA was used to assess data on growth performance, feed utilization, survival rate, digestive enzyme activity, and the amount of lactic acid bacteria, while the hematological parameters were analyzed descriptively. Red tilapia fry weighing an average of 5.27 ± 0.45 g was raised for 30 days in plastic container containing 40 L of water at a density of 15 fish per container (375 fish/m3). Fish were fed three times a day at satiation. Red tilapia-fed diet supplemented with 4 g/kg inulin of feed had higher body weight increase, protein efficiency ratio, digestive enzyme activity, and amount of lactic acid bacteria while food conversion ratio was lower compared to other treatments (p<0.05). Meanwhile, the specific growth rate and survival rate were not different from the control group. Hematological parameters were within the normal range for all treatments. Thus, the supplementation of inulin in feed of 4 g/kg has the potential as a prebiotic for red tilapia. Keywords: digestive enzyme activity, inulin, lactic acid bacteria, prebiotic, red tilapia ABSTRAK Tujuan dari penelitian ini adalah untuk mengkaji pengaruh inulin sebagai prebiotik pada pakan terhadap kinerja pertumbuhan, parameter hematologi, pemanfaatan pakan, aktivitas enzim pencernaan, dan kuantitas bakteri asam laktat di usus ikan nila merah (Oreochromis sp.). Penelitian ini memiliki rancangan acak lengkap dengan empat perlakuan dan tiga ulangan yaitu inulin dengan dosis 0; 1; 2; dan 4 g inulin/kg pakan. One-way ANOVA digunakan untuk menilai data kinerja pertumbuhan, pemanfaatan pakan, kelangsungan hidup, aktivitas enzim pencernaan, dan jumlah bakteri asam laktat, sedangkan parameter hematologi dianalisis secara deskriptif. Benih ikan nila merah dengan berat rata-rata 5,27 ± 0,45 g dipelihara selama 30 hari dalam wadah plastik dengan volume air 40 L dan kepadatan 15 ekor per wadah (375 ekor/m3). Ikan diberi makan tiga kali sehari secara at satiation. Ikan nila merah yang diberi suplemen inulin 4 g/kg pakan menunjukkan pertumbuhan bobot, rasio efisiensi protein, aktivitas enzim pencernaan, dan jumlah bakteri asam laktat yang lebih besar, sedangkan konversi pakan lebih rendah dibandingkan dengan perlakuan lainnya (p<0,05). Parameter laju pertumbuhan spesifik dan tingkat kelangsungan hidup tidak berbeda dengan kelompok kontrol Parameter hematologi berada dalam kisaran normal untuk semua perlakuan. Suplementasi inulin pada pakan sebanyak 4 g/kg berpotensi sebagai prebiotik ikan nila merah. Kata kunci: aktivitas enzim pencernaan, bakteri asam laktat, ikan nila merah, inulin, prebiotik